Instances of unethical performance of academic faculty members in conducting and publishing research works - Rahele Samouei; Narges Meshkineh; Shahin Mojiri (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Today, compliance with ethical principles and standards has become a concern of research ethics committees more than in the past, and the informed society is more demanding of researchers' considerations and adherence. In this regard, a survey was conducted with the aim of determining instances of unethical behavior of faculty members in conducting and publishing research works. MATERIALS AND METHODS: This study was performed cross-sectional with 100 faculty members answering in the form of systematic random sampling from the scientific measurement system of the Ministry of Health of Iran in August 2023 and testing using a checklist containing 32 examples of unethical research behavior. The data were reported using descriptive statistics and analytical methods such as Student's t-test and analysis of variance. RESULTS: The findings of this study showed some instances of unethical practice in the field of research by the respondents, including submitting the article instead of the corresponding author, adding a guest author in the article, mentioning untrue affiliation, not observing the conflict of interest, conducting judgment with connivance, overlapping publications, manipulation of results, and other cases according to the findings of the text of the article, which was reported in professors of the master's degree with a higher average (0.001, 7.12), but according to the gender and academic rank of the respondents, no significant difference was observed in the averages. CONCLUSION: The findings of this study show some clear instances of unethical practices in the field of research among faculty members and academic groups, and it requires targeted planning and more seriousness to investigate and manage its causes. The results of the study can be used for scientific groups and individuals who are directly and indirectly affected by the research results and researchers' performance.